Do CEO Power And Industry Type Affect The CSR Disclosure? - Zahra; Erwin Saraswati; Syaiful Iqbal (Jurnal Reviu Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of CEO Power and industry type on CSR disclosure. The population in this study are companies listed on the IDX during the 2017-2020 period. The research sample was determined by purposive sampling method. This research uses multiple regression analysis method. The results show that CEO Power of a large or strong company has more involvement in expanding or reducing the company's CSR disclosures. The results also show that the type of industry is not a strong character that has an influence on the company's CSR disclosure. CSR disclosure by the company is only one of the reports that function as a means of delivering information, whether used for legitimate acquisitions or as information for external and internal parties.